The Euro-Asian World
XXII, 248 p.
Keywords: This text establishes the concept of Euro-Asia as the means to discuss the European and Asian countries that are undergoing post-Cold War transformation. Elements of the transitional changes covered include: conflicts and peacekeeping, geopolitical issues and economic realities.